2023
DOI: 10.1002/marc.202300177
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Architecture‐Dependent Polymorphous Crystallization Behavior of PVDF in the PVDF/γ‐BL System via Thermally Induced Phase Separation

Florian Gaßdorf,
Zengxuan Fan,
Jan Schwaderer
et al.

Abstract: This study investigates the effect of the macromolecular architecture of poly(vinylidene fluoride) (PVDF) on its thermally induced phase separation (TIPS) behavior and polymorphic crystallization in the PVDF/γ‐butyrolactone (PVDF/γ‐BL) system. Preparative PVDF fractions with specific macromolecular architecture and phase constitution are generated. The results show that PVDF's macromolecular architecture, particularly the degree of branching and regio‐defects, plays a significant role in its temperature‐depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Fischlschweiger and co-workers reported the formation of the γ form of PVDF using γ-butyrolactone and demonstrated that the crystallization temperature of the PVDF solution determines the fractions of the α and γ forms. In the present work, the PVDF gel in γ-butyrolactone shows the predominant γ form . However, unlike the PVDF/cyclohexanone gel, the PVDF/γ-butyrolactone gel shows a crystal–crystal transition upon the solvent exchange process, and the disordered γ form is transformed to the β form, 2θ = 20.7° (110/200) (Figure b, middle panel). , To enhance our understanding of this crystal–crystal transition, we measured WAXD patterns upon systematic exchange at different time intervals (Figure S1).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Fischlschweiger and co-workers reported the formation of the γ form of PVDF using γ-butyrolactone and demonstrated that the crystallization temperature of the PVDF solution determines the fractions of the α and γ forms. In the present work, the PVDF gel in γ-butyrolactone shows the predominant γ form . However, unlike the PVDF/cyclohexanone gel, the PVDF/γ-butyrolactone gel shows a crystal–crystal transition upon the solvent exchange process, and the disordered γ form is transformed to the β form, 2θ = 20.7° (110/200) (Figure b, middle panel). , To enhance our understanding of this crystal–crystal transition, we measured WAXD patterns upon systematic exchange at different time intervals (Figure S1).…”
Section: Resultsmentioning
confidence: 76%
“…It was reported that the PVDF crystalline forms are affected sensitively by the nature of the solvent used and also by the crystallization conditions (temperature and crystallization rate). 62,63 As detailed in the Experimental Section, the gelation solvent was exchanged with ethanol and water before freeze-drying to obtain the respective aerogels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations